A study on histopathological examination of colorectal carcinoma with special reference to expression of CK20 in colorectal adenocarcinoma at a tertiary care centre - Deori, Biman J.; Lahkar, Nandinee; Tabassum, Musfika (International Journal of Research in Medical Sciences, 2021)
Background: Colorectal carcinoma is the third most common cancer worldwide, over 1.8 million new cases are estimated in the year 2018. In terms of mortality, colorectal carcinoma ranks second with estimated 881,000 deaths in 2018. Histopathological study plays a central role for diagnosis and definitive treatment of colorectal carcinoma. In present time, immunohistochemical markers with adjunct to morphology helps in diagnosis and also in prognosis and treatment. Therefore, in colorectal carcinoma, along with morphology, many such immunohistochemical markers are being studied. Methods: This study was carried out in the Department of Pathology at a tertiary care health centre in the southern part of Assam for a period of 1 year from June 2018 to May 2019. 52 cases of colorectal carcinoma diagnosed by histopathological study were included in the study. All patients were analysed for age, gender, type of growth and location of growth. Immunohistochemical staining of cytokeratin (CK) 20 was done and expression was studied and correlated with age, location of tumour, grade and tumour stage. Results: Out of total 52 patients, 33 were male and 19 were female. Average age of presentation was 48.46±15.51 years. On gross examination rectal tumours were the most common and maximum tumours had polypoidal type of growth. On immunohistochemical study CK20 expression was detected in 82.7% out of 52 cases of colorectal adenocarcinoma and negative in 17.3% cases. Conclusions: The correlation between CK20 expression and grading and tumour stages of colorectal adenocarcinoma was statistically significant. Further, large scale population-based studies with more number of cases and follow-up of these cases need to be done for better assessment of this immunohistochemical marker in colorectal adenocarcinoma that can be used for assessment of prognosis.